Internationalization of the spanish economy and the accession to the European Economic Community: economic policy and income distribution (1959-1997) - Raya Rodríguez, Carlos (Papeles de Europa, 2019)
This paper examines the internationalization of the Spanish economy from the sixties to the end of the 20th century, emphasizing the relevance of the accession to the European Economic Community, in order to analyse if that path of internationalization imposed a series of economic policies, firstly the incomes policies and secondly the loss of economic sovereignty, which worked against the income of the working class. For this objective, the marxist method will be used as it offers the best tools to acquire a class perspective.
Keywords: internationalization; distribution; ECC; economic politic; economic polic